Sleep Quality and Life Satisfaction of Railway Employees - Milenović, Miodrag; Milićević, Nebojša; Dimitrijević, Mina (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The aim of the study was to examine the relationship between sleep quality and life satisfaction. The basic hypothesis was that the dimensions of quality and quantity of sleep will be statistically significant predictors of life satisfaction among employees of the Serbian Railways. A total of 126 workers working in different jobs were surveyed: dispatcher, information worker, cashier, train driver, and conductor. Respondents differed according to gender, age, and years of service. The main research variables were operationalized by The Pittsburgh Sleep Quality Index (PSQI; Buysse et al., 1989) and the Satisfaction Life Scale (SWLS; Diener et al., 1985). The results showed that based on the regression model consisting of sleep quality modalities, the criterion variable – life satisfaction (R² = .40, p
Keywords: quality of sleep; life satisfaction; railway employees